Students' Perceptions Toward The Usage Of Technology As Medium For T&l Of Qiraat During Covid-19 - Hayati Hussin; Muhammad Hafiz Saleh; Abd Rahman Abd Ghani; Abdul Rahim Ahmad; Mardhiah Yahaya; Rohana Zakaria (Global Academy of Training and Research(GATR), 2024)
Volume: 7 No: 3 (page:170 – 175)